Experiences, Preferences, and Needs of Adolescents and Urban Youth in Contraceptive Use in Conakry, 2019, Guinea - Bangoura, Charlotte; Dioubaté, Nafissatou; Manet, Hawa; Camara, Bienvenu Salim; Kouyaté, Mariama; Douno, Moussa; Tetui, Moses; El Ayadi, Alison M.; Delamou, Alexandre (Frontiers in Global Women's Health, 2021)
INTRODUCTION: The use of contraceptive methods is very low in Guinea, particularly among adolescents and youth. The purpose of this study is to analyze the experiences and expectations of adolescents and youth regarding the use of contraceptive methods in 2019 in Conakry, Guinea. METHODS: We conducted a six-month qualitative and descriptive study. Data were collected through individual in-depth interviews and focus group discussions with adolescents and youth, health providers and health policymakers. Two approaches of deductive and inductive analysis were used to synthesize the main insights from the data. FINDINGS: 56 participants were included in this study. Adolescents and youth have personal, family and community experiences that positively or negatively influence their contraceptive needs and preferences. Positive experiences include the relative cost of injectable forms, perceived absence of side effects of implants, proven efficacy and duration of action of the modern method used (implants and injectable form). Negative experiences included the cost of implants remain high (15 Euros), perceived side effects including weight gain, pill compliance, method indiscretion, and low sensation of sexual pleasure for the condom. The preferences of the young participants were dominated by Implants and injectable forms that better meet their contraceptive needs. In terms of needs, the expectations expressed revolved around needs related to the health system, including sex education, reduction in the cost of some contraceptives (implants), availability of contraceptive methods, and equity in the provision of family planning services to adolescents and youth. CONCLUSION: Exploring the contraceptive experiences, needs and preferences of adolescents and youth reveal decision-making dilemmas. Adolescents and youth expressed their experiences in terms of the cost of preferred contraceptives (implants), side effects, proven efficacy, and duration of action. However, their decisions are still influenced by availability, equity in service delivery, and the involvement of parents and religious leaders in sex education. Decision-makers should then place particular emphasis on improving health service delivery, adolescent sexual and reproductive health, availability of preferred contraceptive methods at affordable cost, and a program on sexuality education with the involvement of parents and religious leaders and the promotion of condom use.